Heterotrophic Nitrification in an Acid Forest Soil and by an Acid-Tolerant Fungus - Stroo, Hans F. (1986)
Nitrate was formed from ammonium at pH 3.2 to 6.1 in suspensions of a naturally acid forest soil; the maximum rates of formation occurred at ca. pH 4 to 5. Nitrate was also formed from soil nitrogen in suspensions incubated at 50°C. Autotrophic nitrifying bacteria could not be isolated from this soil. Enrichment cultures produced nitrate in a medium with β-alanine if much soil was added to the medium, and nitrite but not nitrate was formed in the presence of small amounts of soil. Nitrification by these enrichments was abolished by eucaryotic but not procaryotic inhibitors. A strain of Absidia cylindrospora isolated from this soil was found to produce nitrate and nitrite in a medium with β-alanine at pH values ranging from 4.0 to 4.8. Nitrate production by A. cylindrospora required the presence of sterile soil. Free and bound hydroxylamine, hydroxamic acids, and primary aliphatic nitro compounds did not accumulate during the conversion of β-alanine to nitrite by the fungus. The organism also formed nitrite from ammonium in a medium containing acetate. We suggest that nitrification in this soil is a heterotrophic process catalyzed by acid-tolerant fungi and not by autotrophs or heterotrophs in nonacid microsites.